Perception of Purposeful and Recreational Smartphone Use in Physiotherapy: Randomized Controlled Trial - Bientzle, Martina (JMIR Mhealth Uhealth, 2021)
BACKGROUND: Many people constantly use their smartphones in all kinds of situations. Often smartphones are used in a meaningful and targeted way, but frequently they are used as a pastime without any purpose. This also applies to patients and therapists in treatment situations. OBJECTIVE: The aim of this study was to investigate how purposeful smartphone use compared with recreational smartphone use (by a physiotherapist or by a patient) influenced the perception of a physiotherapeutic treatment situation. We examined the impact of smartphone use during a physiotherapy session on the perception of the physiotherapist, evaluation of attentiveness, and evaluation of smartphone use in physiotherapy in general. METHODS: Members of various music and sports clubs were invited to participate in an online randomized controlled trial. Participants were randomly assigned to one of four conditions. They watched a video in which a physiotherapeutic treatment was shown and in which a smartphone was used or not used in the following four different ways: (1) therapeutically purposeful use, (2) recreational use by the physiotherapist (looking at the phone from time to time with no therapeutic purpose), (3) recreational use by the patient, and (4) no smartphone use (control condition). After watching the video, the participants indicated their perception of the physiotherapist’s professional competence, social competence, and empathetic behavior. They also rated the physiotherapist’s and patient’s attentiveness and evaluated the usage of smartphones generally in physiotherapy. RESULTS: The analysis included 118 participants (63 women and 55 men). When the physiotherapist used the smartphone in a purposeful way, the physiotherapist was perceived as more professionally competent (P=.007), socially competent (P=.03), and empathetic (P=.04) than if the physiotherapist used it with no therapeutic purpose. These effects occurred because recreational smartphone use by the physiotherapist was evaluated more negatively than the behavior in the control condition (professional competence: P=.001; social competence: P=.03; empathy: P=.04). Moreover, when the physiotherapist used the smartphone in a recreational way, the physiotherapist was perceived as being less attentive (P<.001). Likewise, when the patient used the smartphone in a recreational way, the patient was perceived as being less attentive (P<.001). Finally, smartphone use in physiotherapy was rated as more positive in general when the smartphone was used in a purposeful way compared with the conditions in which the physiotherapist or patient looked at the smartphone with no therapeutic purpose (P<.001). This positive evaluation occurred because purposeful use led to a more positive rating than no smartphone use (P<.001, R=0.42). CONCLUSIONS: Smartphones are only appropriate for therapists and patients if they are used directly for a therapeutic purpose. Otherwise, it is better not to use smartphones during treatment. TRIAL REGISTRATION: AsPredicted (aspredicted.org) #24740; https://aspredicted.org/blind.php?x=vv532i